Study on Long-Distance Electric Mobility on a Multinational Route - Velizara Pencheva; Asen Asenov; Mladen Kulev (World Electric Vehicle Journal)
This study explores the challenges associated with long-distance travel exceeding 2000 km using an electric vehicle (EV) on a route spanning multiple countries, from Bulgaria to France. A dedicated research methodology was developed, selecting a specific route and EV for analysis. The findings indicate that the energy consumption along the entire route averaged approximately 0.18 kWh/km under a load of around 240 kg. Furthermore, the study identified key challenges faced by EV drivers, particularly in locating charging stations and securing electric energy supply. Based on the results, several recommendations are proposed to enhance charging infrastructure conditions and mitigate driver uncertainty.